A Wearable Sensing Framework for Improving Personal and Oral Hygiene for People with Developmental Disabilities - Wijayasingha,L; Lo,BPL (IEEE, 2016)
People with developmental disabilities often facedifficulties in coping with daily activities and many requireconstant support. One of the major health issues for peoplewith developmental disabilities is personal hygiene. Many lackthe ability, poor memory or lack of attention to carry outnormal daily activities like brushing teeth and washing hands.Poor personal hygiene may result in increased susceptibility toinfection and other health issues. To enable independent livingand improve the quality of care for people with developmentalabilities, this paper proposes a new wearable sensingframework to monitoring personal hygiene. Based on asmartwatch, this framework is designed as a pervasivemonitoring and learning tool to provide detailed evaluation andfeedback to the user on hand washing and tooth brushing. Apreliminary study was conducted to assess the performance ofthe approach, and the results showed the reliability androbustness of the framework in quantifying and assessing handwashing and tooth brushing activities.